DevGo: um modelo para governança de desenvolvedores em ecossistema de software móvel a partir de developer relations - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
Organizations that maintain mobile software ecosystems (MSECO), such as Apple, Google and Microsoft, have engaged a critical mass of outside developers to expand their platforms. As such, they explore strategies for developer governance. These strategies depend on the associated operation between the organization's goals and the expectations of the developers. The MSECO developer governance area still needs formalization, theories and models. In this context, organizations have invested in Developer Relations (DevRel).The industry requires new strategies that promote the organization's collaboration with external developers. As part of these strategies, DevRel professionals need to have a realistic view of developers' behavior within the ecosystem and then meet the developers’ needs and achieve organizations’ goals. The definition of developer governance strategies is not trivial; it consists of delimiting the actions of developers without restricting excessively the desired level of value creation. If developer governance is unsustainable, it can lead to the "death" of the ecosystem. For example, one of the factors by which the Windows Phone MSECO was officially declared "dead" in 2017 was because the developers no longer supported the platform. In this thesis, through a set of secondary and primary studies and mining software repositories involving DevRel professionals, we investigate the structure of MSECO developer governance and a set of lessons learned. Next, we built and refined a model for governance of developers in MSECO called DevGo (DEVeloper GOVernance). DevGo consists of: areas of focus, developer advancement stages, stages, facilitators, and value transfer objects. In addition, a set of lessons learned from DevRel professionals associated with DevGo stages, repository categories, and motivations for their use with a focus on monitoring. From the case studies, participants noted that the DevGo framework facilitates understanding of developer governance, value transfer objects, as well as the communication of the importance of the field to the organization and the focus area regarding ecosystem monitoring. There was no disagreement regarding the adequacy, control, understanding and generality of DevGo.
DevGo: a developer governance model in mobile software ecosystem from devrel
Keywords: Software - Desenvolvimento; Ecossistemas de software; Aplicativos para dispositivos móveis; CIÊNCIAS EXATAS E DA TERRA: CIÊNCIA DA COMPUTAÇÃO: METODOLOGIA E TÉCNICAS DA COMPUTAÇÃO: ENGENHARIA DE SOFTWARE; Modelo; Ecossistema de software; Aplicação móvel; Governança; Recomendações; Developer relations; Desenvolvedores